1996
DOI: 10.1093/ajcp/105.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-associated Gastric Adenocarcinomas Among Koreans

Abstract: Epstein-Barr virus (EBV)-associated gastric carcinomas have been reported from various regions of the world. Epstein-Barr virus appears to be pathogenetically related to some gastric carcinomas. To determine the incidence of EBV association with gastric carcinomas among Koreans, the authors have studied EBV genome expression in 89 consecutive patients with gastric carcinomas diagnosed at the Catholic University Hospitals in Seoul, Korea, using in situ hybridization (ISH) for EBV-encoded small RNAs (EBERs), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 0 publications
6
36
0
Order By: Relevance
“…Occurrence in elderly persons and male predominance are common in EBV-associated gastric carcinomas (23,25,27,29,(31)(32)(33)(34)(35)(36)(37), and these findings were also observed in the present study. However, the site where EBVpositive gastric carcinoma more often arises is a controversial issue in the literature.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Occurrence in elderly persons and male predominance are common in EBV-associated gastric carcinomas (23,25,27,29,(31)(32)(33)(34)(35)(36)(37), and these findings were also observed in the present study. However, the site where EBVpositive gastric carcinoma more often arises is a controversial issue in the literature.…”
Section: Discussionsupporting
confidence: 89%
“…The frequency of EBV-positive gastric carcinomas can reach up to 18% (19,21,23,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), as reported in Germany (39). In Eastern countries, e.g., Japan, China and Taiwan, EBV-positive gastric cancer comprises 5.6 to 13.5% of cases (19,21,(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…LMP is not expressed in EBV-associated gastric carcinomas, 15,16,25,26) except in a few cases. 6,17,27) Our two cell lines revealed a patchy distribution of LMP1, as seen in other types of cell lines, 28,29) although the expression of LMP1 was relatively low in GT39 cells. It has been reported that the expression of LMP is tightly regulated by cellular factor(s), 30) and that LMP is not expressed in EBV-infected epithelial cell lines, except after addition of differentiating agents.…”
Section: Characterization Of Cell Linessupporting
confidence: 66%
“…EBV-positive gastric cancers are more likely in males compared with females (Shibata and Weiss, 1992;Tokunaga et al, 1993), less likely to be found in the gastric antrum than in the cardia or body of the stomach Yuen et al, 1994;Galetsky et al, 1997), and more likely to be poorly differentiated tumours (Yuen et al, 1994;Gulley et al, 1996;Shin et al, 1996;Galetsky et al, 1997). Less consistent associations have been found for age, with some studies finding more EBV-positive tumours in older people, 60 þ years (Qiu et al, 1997) or 56 þ years (Gulley et al, 1996).…”
Section: Gastric Carcinomamentioning
confidence: 99%